The evolving role of traditional birth attendants in maternal health in post-conflict Africa: A qualitative study of Burundi and northern Uganda - Chi, Primus Che (SAGE Open Med, 2018)
OBJECTIVES: Many conflict-affected countries are faced with an acute shortage of health care providers, including skilled birth attendants. As such, during conflicts traditional birth attendants have become the first point of call for many pregnant women, assisting them during pregnancy, labour and birth, and in the postpartum period. This study seeks to explore how the role of traditional birth attendants in maternal health, especially childbirth, has evolved in two post-conflict settings in sub-Saharan Africa (Burundi and northern Uganda) spanning the period of active warfare to the post-conflict era. METHODS: A total of 63 individual semi-structured in-depth interviews and 8 focus group discussions were held with women of reproductive age, local health care providers and staff of non-governmental organisations working in the domain of maternal health who experienced the conflict, across urban, semi-urban and rural settings in Burundi and northern Uganda. Discussions focused on the role played by traditional birth attendants in maternal health, especially childbirth during the conflict and how the role has evolved in the post-conflict era. Transcripts from the interviews and focus group discussions were analysed by thematic analysis (framework approach). RESULTS: Traditional birth attendants played a major role in childbirth-related activities in both Burundi and northern Uganda during the conflict, with some receiving training and delivery kits from the local health systems and non-governmental organisations to undertake deliveries. Following the end of the conflict, traditional birth attendants have been prohibited by the government from undertaking deliveries in both Burundi and northern Uganda. In Burundi, the traditional birth attendants have been integrated within the primary health care system, especially in rural areas, and re-assigned the role of ‘birth companions’. In this capacity they undertake maternal health promotion activities within their communities. In northern Uganda, on the other hand, traditional birth attendants have not been integrated within the local health system and still appear to undertake clandestine deliveries in some rural areas. CONCLUSION: The prominent role of traditional birth attendants in childbirth during the conflicts in Burundi and northern Uganda has been dwindling in the post-conflict era. Traditional birth attendants can still play an important role in facilitating facility and skilled attended births if appropriately integrated with the local health system.